2017
DOI: 10.1111/evo.13273
|View full text |Cite
|
Sign up to set email alerts
|

Relating quantitative variation within a behavior to variation in transcription

Abstract: Many studies have shown that variation in transcription is associated with changes in behavioral state, or with variation within a state, but little has been done to address if the same genes are involved in both. Here we investigate the transcriptional basis of variation in parental provisioning using two species of burying beetle, Nicrophorus orbicollis and Nicrophorus vespilloides. We used RNA-seq to compare transcription in parents that provided high amounts of provisioning behavior versus low amounts in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 70 publications
(148 reference statements)
4
27
0
Order By: Relevance
“…Genes previous found to be differentially expressed in N. vespilloides when transitioning from a completely non-parenting to parenting statesuch as vitellogenin 1, vitellogenin 2 and their receptor (vg1, vg2 and vgr;Roy-Zokan et al, 2015), and neuropeptide f and its receptor, npfr (Cunningham et al, 2016) were not involved in the subtler plasticity examined here. Benowitz et al (2017) sampled N. vespilloides and Nicrophorus orbicollis males and females that contrasted the transcriptional architecture of high versus low direct care expressed by parents in a 2×2×2 design. Their study found very subtle differences of transcription associate with the level of direct care expressed by parents.…”
Section: Gene Expression and Differing Forms Of Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…Genes previous found to be differentially expressed in N. vespilloides when transitioning from a completely non-parenting to parenting statesuch as vitellogenin 1, vitellogenin 2 and their receptor (vg1, vg2 and vgr;Roy-Zokan et al, 2015), and neuropeptide f and its receptor, npfr (Cunningham et al, 2016) were not involved in the subtler plasticity examined here. Benowitz et al (2017) sampled N. vespilloides and Nicrophorus orbicollis males and females that contrasted the transcriptional architecture of high versus low direct care expressed by parents in a 2×2×2 design. Their study found very subtle differences of transcription associate with the level of direct care expressed by parents.…”
Section: Gene Expression and Differing Forms Of Plasticitymentioning
confidence: 99%
“…An outstanding question is how much gene expression is associated with each source of variation when more than one factor is manipulated. Assessing the influence of multiple factors requires examining those factors with experimental designs that minimize other differences that can exist when examining highly distinct behavioural states (Benowitz et al, 2017;Kronauer and Libbrecht, 2018) and that allow a partitioning of effects. Furthermore, the mechanisms that regulate the variation of gene expression differences are not fully characterized, but need to be to fully understand of the evolution and mechanistic basis of behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An outstanding question is how much gene expression belongs to plasticity of behavioural state, social context, and individual flexibility. This question requires examining factors of interest at the same time and with experimental designs that minimize other differences that can exist when examining highly distinct behavioural states (Benowitz et al, 2017). Furthermore, the mechanisms that regulate gene expression variation are not fully characterised, but are needed for a full understanding of the evolution and mechanistic basis of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…This helps us directly isolate potential effects on gene expression from behavioural state, social context, and individual flexibility displayed for those behaviours (Table 1). This is important because social behaviour is multifaceted and moving to factorial designs helps us to begin disentangling the influence of single variables, rather than comparing gene expression across behavioural states that necessarily differ for many variables (Lockett et al, 2012; Benowitz et al, 2017). We also have a sequenced and annotated genome for N. vespilloides , and there is gene body cytosine methylation (Cunningham et al, 2015).…”
Section: Introductionmentioning
confidence: 99%